The Effect of Maqashid Syariah toward Human Development Index: Evidence from Indonesia - Haraki, Emil; Widuri, Citra; Jaenudin, M; Nadofah, Nadofah (ITB AAS INDONESIA Surakarta, 2024)
Indonesia's level of social welfare as represented using the Human Development Index is always below the world average, and until now there has been no proper handling to make Indonesia's HDI score above the world's average HDI score. This study aims to see the effect of each point of Maqashid Syariah on the increase and decrease in Indonesia's HDI. The data used is secondary data from the world bank, Transparency International, and BPS. The data was taken over 10 years, starting from 2011 – 2020. The method used to see the effect was a multiple regression model, and carried out several classical assumption tests, such as tests for normality, serial correlation, variance inflation factors and heteroscedasticity. The results of this study are that at each point of Maqashid Syariah there is Zakat in faith (diin), Poverty Rate in Human Life (Nafs), Literacy rate in Intellect ('Aql), Mortality rate in Posterity (Nasl), and Employment in Wealth (Maal), that has an influence on HDI and Corruption Perception Index (diin), Life Expectancy (Nafs), Education Spending Rate (‘Aql), Birth Rate (Nasl), and GDP Per Capita has not influence on HDI (Maal).